Analisis Urf terhadap Jual Beli Tembakau dengan Sistem Tebbhesen : (Studi Kasus di Desa Karang Penang Onjur Sampang) - Harisah Harisah; Zainulloh Zainulloh; Wasilah Wasilah (Journal of Economic and Islamic Research, 2023)
Increasing the results of agricultural sales in the community of an area is one of the factors for improving the community's economy, especially in the agricultural sector which is considered profitable by the community, one of the tobacco farming sectors which is one of the most profitable livelihoods in rural communities, as well as in Karang Penang Village Onjur Sampang. However, the tobacco season sometimes becomes a bad season due to an inadequate buying and selling system, such as buying and selling using the tebbhesen system (Madura language). This research was conducted using qualitative methods using interviews. Observation and documentation. The interviews were conducted directly with farmers, middlemen, and traders to obtain valid data. In addition to the interviews, observations were made by researchers by looking at buying and selling practices in the field and coupled with data documentation in the field. This research results that in the view of urf sell tebbhesen this is not valid because it contains losses to one of the parties. Losses are not always experienced by farmers, sometimes they are felt by middlemen and sometimes also experienced by traders because there is no certainty of yields from the tobacco they buy.